Pattern Of Increasing Organizational Performance With Position Of Promotion Policy And Work Productivity Approach An Empirical Study On Public Organizations Sector Jabodetabek - Usman Effendi (Jurnal Serambi Ilmu, 2024)
The main purpose of this study is to find out the extent of the influence of job promotion policies and work productivity on improving organizational performance in Ministries and Government Agencies. The object of this research is the State Civil Apparatus who work in Ministries and Government Institutions of the Republic of Indonesia in the city of Jakarta and its surroundings. The research method used is descriptive, which only aims to describe and explain the characteristics of a situation at a certain time in order to provide an overview of the relationship between job promotion and work productivity with organizational performance. The data collection technique used a questionnaire, which was distributed incidentally to the object of research in Jakarta and its surroundings. The results of this study found that there was a partial effect of job promotion policies on organizational performance, significant and there was a positive relationship. Meanwhile, work productivity has no partial effect on organizational performance and has a negative relationship. Simultaneously, it was found that there was an influence between the policy of promotion and work productivity on organizational performance, but it was not significant, it turned out that the policy of promotion was very decisive in improving the performance of public organizations.